1994
DOI: 10.1007/bf00389543
|View full text |Cite
|
Sign up to set email alerts
|

A set of 99 cattle microsatellites: characterization, synteny mapping, and polymorphism

Abstract: Cattle microsatellite clones (136) were isolated from cosmid (10) and plasmid (126) libraries and sequenced. The dinucleotide repeats were studied in each of these sequences and compared with dinucleotide repeats found in other vertebrate species where information was available. The distribution in cattle was similar to that described for other mammals, such as rat, mouse, pig, or human. A major difference resides in the number of sequences present in the bovine genome, which seemed at best one-third as large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(126 citation statements)
references
References 35 publications
5
108
0
8
Order By: Relevance
“…The PIC value is commonly used in genetics as a measure of polymorphism for a marker locus used in linkage analysis (Matin et al 2012). Table 3 showed that PIC values varied greatly for all the SSR loci tested with an average of 0.61 indicating that the primers could develop high polymorphism which is useful for assessing genetic variation of genotypes studied in this research (Vaiman et al 1994). The PIC values revealed are comparable to those reported for faba bean cultivars in other countries such as Korea.…”
Section: Discussionsupporting
confidence: 63%
“…The PIC value is commonly used in genetics as a measure of polymorphism for a marker locus used in linkage analysis (Matin et al 2012). Table 3 showed that PIC values varied greatly for all the SSR loci tested with an average of 0.61 indicating that the primers could develop high polymorphism which is useful for assessing genetic variation of genotypes studied in this research (Vaiman et al 1994). The PIC values revealed are comparable to those reported for faba bean cultivars in other countries such as Korea.…”
Section: Discussionsupporting
confidence: 63%
“…Microsatellite sequence isolation from these 39 bovine BAC clones was performed according to standard procedures (Vaiman et al 1994). The protocol was slightly improved to increase the yield.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of the loci are shown in Supplementary Figure S2. They were typed using 20-30 ng of DNA in PCR protocols on an MJ Research PTC 200 Peltier Thermal Cycler (MJ Research Inc., MA, USA) with a hot lid: INRA124 (Vaiman et al, 1994), INRA126 (Vaiman et al, 1994), INRA189 (Kappes et al, 1997) and BM861 (Bishop et al, 1994) were according to Edwards et al (2000), and BYM-1 (Matthews and Reed, 1991) according to Ward et al (2001). The size characterization of PCR products was carried out on a Pharmacia ALF-express Automated Sequencer for loci INRA124, INRA126, INRA189 and BM861, and on an Amersham MegaBACE 500 DNA Sequencer for locus BYM-1.…”
Section: Y-chromosome Microsatellite Typingmentioning
confidence: 99%